Fennel (Foeniculum vulgare) leaf infusion effect on mammary gland activity and kidney function of lactating rats - NAJDA RIFQIYATI; ANA WAHYUNI (Nusantara Bioscience, 2019)
Abstract. Rifqiyati N, Wahyuni A. 2019. Fennel (Foeniculum vulgare) leaf  infusion effect on mammary gland activity and kidney function of lactating rats. Nusantara Bioscience 11: 101-105. Fennel (Foeniculum vulgare Mill) leaf, traditionally, is believed to have a potential in increasing and smoothing breast milk production. This study aimed to determine the effect of fennel leaf infusion on milk production and to know the side effects of its use. The material used in the research was infusion of fennel leaves (Foeniculum vulgare Mill) collected from Kopeng, Central Java. The research utilized 12 female rats each with 5 newborns off springs. The experiment was designed in Completed Random Design (CRD) with 4 treatments and 3 replications. Histological preparation of mammary glands was set using paraffin method with HE staining. Kidney function was observed through uric acid level in the blood. The results showed that the diameter of lactiferous ducts and of its lumen diameter were significantly influenced by 15 days fennel leaf infusion treatment. The largest lactiferous duct diameter observed was on P3 treatment group (452.97 ± 75.033 µm) and the smallest was observed in control groups (273.17 ± 38.746 µm). The numbers of active alveoli observed in treatment groups, i.e., in P1 (20 g/300  mL), P2 (40 g/300  mL), and P3 (60 g/300  mL), increased than inactive alveoli. The blood uric acid level observed was 4.0-4.6 mg/dl. The results suggested that the infusion of fennel leaf with a treatment dose of 60 g infusion in 300  mL distilled water administered for 15 days can significantly increase the diameter of lactiferous lumen of female rat mammary glands, and increase the diameter of the alveoli and the number of active alveolar mammary glands. Histological picture of mammary gland also showed that the female rats treated with dose of 60g infusion per 300  mL aquadest increased milk secretion and than the other treatment groups. The treatment also showed no significant side effects.